THE SIGNIFICANCE OF SOCIOLINGUISTIC DETERMINANTS IN SHAPING THE LANGUAGE UTILIZED WITHIN CONTEMPORARY MASS MEDIA OUTLETS: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores the crucial role of sociolinguistic factors in influencing the language employed within modern mass media platforms. Sociolinguistics, as a field of study, delves into the interaction between language and society, shedding light on how social factors shape linguistic norms and practices. In the context of mass media, sociolinguistic determinants play a pivotal role in determining language choices, styles, and discourses, reflecting and shaping societal attitudes, identities, and power dynamics. This study conducts a comprehensive analysis of relevant literature, investigates the methodologies employed in researching sociolinguistic phenomena in media discourse, and presents key findings regarding the impact of sociolinguistic factors on language usage within contemporary mass media outlets.